Performance of Elecsys® HCV Duo Immunoassay for Diagnosis and Assessment of Treatment Response in HCV Patients with or without HIV Infection - Prooksa Ananchuensook; Jongkonnee Wongpiyabovorn; Anchalee Avihingsanon; Pisit Tangkijvanich (Diagnostics)
Background/Objectives: The Elecsys® HCV Duo immunoassay (Roche Diagnostics International Ltd., Rotkreuz, Switzerland) detects both antibodies to hepatitis C virus (anti-HCV) and HCV core antigen (HCV-Ag) and has shown excellent diagnostic performance in blood donor samples. We aim to validate its use for diagnosing chronic HCV infection and assessing sustained virological response (SVR) post-direct-acting antivirals (DAAs) in patients with or without HIV infection. Methods: Blood samples from 100 healthy controls, as well as 64 HCV mono-infection and 136 HCV-HIV coinfections, were collected before and 12–24 weeks after DAAs. The assay performance for determining active infection at baseline and SVR was compared with HCV RNA. Results: Overall, 156 (78.0%) of HCV-infected patients had HCV genotype 1, and the SVR rate was 96.5%. The sensitivity, specificity, and area under the ROC curve (AUROC) for HCV diagnosis at baseline were 99.50% (95% confidence interval [CI], 96.82–99.97%), 100% (95%CI, 95.39–100%), and 0.998 (95%CI, 0.992–1.003), respectively. The corresponding results for HCV-Ag in determining SVR were 57.14% (95%CI, 20.24–88.19%), 97.41% (95%CI, 93.73–99.04%), and 0.773 (95%CI, 0.543–1.003), respectively. The assay also exhibited comparable sensitivity and specificity between HCV mono- and coinfection. Conclusions: Our study showed that the Elecsys® HCV Duo immunoassay effectively diagnosed HCV infection, regardless of HIV status, making it suitable for managing high-risk populations in resource-limited settings.